(untitled) (UNED Research Journal, 2017)
The productive and reproductive indexes allow to know the efficiency of the cattle production systems. To evaluate the efficiency of 23 farms located in the South area of Costa Rica, I analyzed the data of the productive and reproductive indexes of 618 bovine animals, during the year 2010 and 2011. The parameters evaluated were weaning, birth weight, weaning weight, age at first calving, calving interval and days open; the average values were 237±5 days, 178,1±25,1Kg/animal, 36±6Kg/animal, 31 months, 459,6±95,3 days and 176,8±95,5 days respectively. The breed of animals, the technological level of the farm according to environmental management, the sanitary program, reproductive management and the technological level in the cultivation of the forage, the training processes and the technology transfer that received the products interfere in the variability observed in the parameters. This information is the basis to bring forward changes in nutritional, sanitary and reproductive management of each system with the objective of increasing the kilograms of live weight produced by animal, decreasing the days between reproductive events and increasing the life of the livestock.